2017
DOI: 10.1016/j.nlm.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The ‘affect tagging and consolidation’ (ATaC) model of depression vulnerability

Abstract: Please cite this article as: Harrington, M.O., Pennington, K., Durrant, S.J., The 'Affect Tagging and Consolidation' (ATaC) Model of Depression Vulnerability, Neurobiology of Learning and Memory (2017), doi: http://dx.doi.org/10. 1016/j.nlm.2017.02.003 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 137 publications
0
10
0
Order By: Relevance
“…Another important line of research which should be pursued in the future relates to the possible relationship between biased encoding mechanisms and REM sleep in the development of emotional memory bias in depression. As discussed, the marginally greater consolidation of negative memories during late sleep in the higher BDI-II score group in this study may be related to increased amygdala activity during the encoding of negative images in this group (Bennion et al, 2015;Costafreda et al, 2013;Dannlowski et al, 2010;Harrington et al, 2017). Future research in this area will benefit from the inclusion of fMRI scanning during encoding phases to determine whether amygdala activity during encoding interacts with REM sleep in the development of negative memory bias.…”
Section: Mmentioning
confidence: 71%
See 2 more Smart Citations
“…Another important line of research which should be pursued in the future relates to the possible relationship between biased encoding mechanisms and REM sleep in the development of emotional memory bias in depression. As discussed, the marginally greater consolidation of negative memories during late sleep in the higher BDI-II score group in this study may be related to increased amygdala activity during the encoding of negative images in this group (Bennion et al, 2015;Costafreda et al, 2013;Dannlowski et al, 2010;Harrington et al, 2017). Future research in this area will benefit from the inclusion of fMRI scanning during encoding phases to determine whether amygdala activity during encoding interacts with REM sleep in the development of negative memory bias.…”
Section: Mmentioning
confidence: 71%
“…According to the Affect Tagging and Consolidation (ATaC) model, heightened amygdala activity during the encoding of negative memories interacts with REM sleep alterations to promote the development of negative memory bias in individuals vulnerable to MDD (Harrington et al, 2017). It is well reported that MDD patients exhibit greater amygdala reactivity to negative emotional stimuli than healthy controls (Costafreda et al, 2013;Perlman et al, 2012;Stuhrmann et al, 2013;Suslow et al, 2010), and amygdala reactivity to negative words has been shown to correlate positively with BDI-II scores in healthy participants (BDI-II score range = 0 -10; Laeger et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional memory biases have been observed in a range of psychopathological conditions (for a review see Haas & Canli, 2008) and have been linked with atypical encoding, consolidation, and retrieval processes. For example, patients with depression tend to remember the bad and forget the good, and there is some evidence that these negative memory biases are associated with disruptions in sleep-dependent memory consolidation processes (Goerke, Muller, & Cohrs, 2017; Harrington, Pennington, & Durrant, 2017). Patients with post-traumatic stress disorder (PTSD) show enhanced memory for trauma-related stimuli and poorer memory for emotionally neutral stimuli compared to controls (Brewin, Kleiner, Vasterling, & Field, 2007) and aberrant activation of occipital cortex during negative memory retrieval (Whalley et al, 2013).…”
Section: A New Model Of Emotional Memory That Emphasizes the Importanmentioning
confidence: 99%
“…Recurrent, self-reflected, and uncontrollable rumination is one of the hallmarks of disease phenomenology (Nolen-Hoeksema et al, 2008;Hamilton et al, 2015;Whisman et al, 2020). Furthermore, depression is associated with negative biases in cognition, which predispose depressed individuals to exhibit a better recall for negative information compared with healthy subjects (Harrington et al, 2017). Patients suffering from depression may avoid social interaction and linger in despair and suicidal thoughts, often with tragic consequences.…”
Section: Introductionmentioning
confidence: 99%